NILAI – NILAI AKHLAK ISLAM DALAM IKLAN TEH BOTOL SOSRO SEMEJA BERSAUDARA DI YOUTUBE - Faiq Tasyrifil Huda; Muhmmad Rikzam Kamal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2021)
The goal of this study is to look for elements of Islamic moral values in some scenes in the Teh Botol Sosro Semeja Brothers advertisement, as well as the use of research as advertising knowledge and information on advertising videos with elements of Islamic values, particularly in the Teh Botol Sosro Semeja Brothers advertisement. In this study, a descriptive qualitative research approach is used, and the research process on an object uses primary and secondary data, with primary data being video files from the Teh Botol Sosro Semeja Bersaudara advertisement as the first source, secondary data being information from books and digital media as the object of Tea advertising research. The Table of the Brothers Bottle from Sosro, the semiotic analysis of Roland Barthes provides strategies for grouping information through observation and documenting, as well as data processing procedures such as editing, arranging, and discovering the findings. The findings of the one-minute study of the Teh Botol Sosro Semeja Brothers advertising found numerous scenarios illustrating Islamic moral principles, including caring for others, sharing among others, being thankful in all circumstances, mutual respect, and tolerance for diversity.